Health Information Management Education at the Institute of Health Policy and Management of the Erasmus University Medical Center - Aarts, J.E.C.M.; Berg, M.; Huisman, E. (Yearbook of Medical Informatics, 2003)
This paper presents a review of the philosophy and content of the Master course of Health Information Management that is being taught at the Institute of Health Policy and Management of the Erasmus University Medical Center in Rotterdam, the Netherlands. We present our experiences of teaching this master course, including its predecessor. Our work, both teaching and researching, can be characterized by the sociotechnical approach of health informatics, which means that we focus on the interrelation of technology and its social environment.